Predicting Job Performance Based on Humor Components and Mental Health among Staff of Ziaeyan Hospital - narges tankamani; majid saffari nia; leila ghobadi (Tehran University of Medical Sciences, 2017)
Background: Hospital staffs including physicians, nurses and crew are exposed to various risks including physical and mental illnesses. The study aimed at predicting job performance based on humor components and mental health among staff of Ziaeyan hospital. Materials and Methods: This study was a descriptive- analytical one. Sample size was 120 individuals (74 females and 46 males) who selected via non- randomly and Voluntary With a diverse range of staff including nurses, physicians in 2014.  After explaining about  research type and filling voluntary questionnaires with informed consent, job performance Paterson, Martin et al humor components  and Goldberg mental health instruments were disseminated. SPSS Software version 17 utilized to data analysis using regression and cluster analysis. Results: Among of humor components and mental health, Self-enhancing, depression and social performance predicted job performance positively. Depression has the largest ß coefficient(0.26)  for job performance  which revealed this variable the strongest one  and provided main contribution to explain the criterion variable. Also, there was a statistically difference between negative morbid humor clusters and positive and healthy clusters of humor in the significant level less than 0.05(t= -7.97, p<0.001). Conclusion: Selection of humor style and enhancing mental health of hospital staff will cause job performance improvement. Regarding stressful environment of hospital, it seems providing better mental health and applying healthy styles of humor as a proper way to staff performance improvement which should be considered.